Inhalable Anti-EGFR Antibody-Conjugated Osimertinib Liposomes for Non-Small Cell Lung Cancer - Apoorva Daram; Shruti S. Sawant; Dhwani A. Mehta; Carlos A. Sanhueza; Nitesh K. Kunda (Pharmaceutics)
Background: Non-small cell lung cancer (NSCLC) is a leading cause of cancer deaths globally. The most extensive treatment is Tyrosine Kinase Inhibitors (TKIs) that target epidermal growth factor receptor (EGFR) overexpression. Osimertinib, a third-generation TKI is approved to target EGFR exon 19 deletions or exon 21 L858R mutations. However, resistance is inevitable due to emergence of triple mutations (sensitizing mutations, T790M and C797S). To overcome this challenge, a combinatorial approach was used wherein Osimertinib liposomes were conjugated with cetuximab (CTX), an anti-EGFR monoclonal antibody, to improve drug efficacy and delivery. Additionally, pulmonary administration was employed to minimize systemic toxicity and achieve high lung concentrations. Methods: Osimertinib liposomes (OB-LPs) were prepared using thin film hydration method and immunoliposomes (CTX-OB-LPs) were prepared by conjugating the OB-LPs surface with CTX. Liposomes were characterized for particle size, zeta-potential, drug loading, antibody conjugation efficiency, in vitro drug release, and aerosolization performance. Further, the in vitro efficacy of immunoliposomes was evaluated in H1975 cell line. Results: Immunoliposomes exhibited a particle size of 150 nm, high antibody conjugation efficiency (87%), efficient drug release, and excellent aerosolization properties with an aerodynamic diameter of 3 μm and fine particle fraction of 88%. Furthermore, in vitro studies in H1975 cells showed enhanced cytotoxicity with CTX-OB-LPs displaying 1.7-fold reduction and 1.2-fold reduction in IC50 compared to Osimertinib and OB-LPs, respectively. The CTX-OB-LPs also significantly reduced tumor cell migration and colonization compared to Osimertinib and OB-LPs. Conclusions: These successful results for EGFR-targeting inhalable immunoliposomes exhibited potential for contributing to greater anti-tumor efficacy for the treatment of non-small cell lung cancer.